Vertical alignment of polyaniline nanofibers on electrode surface for high-performance microbial fuel cells. (September 2019) - Zhai, Dan-Dan; Fang, Zhen; Jin, Hongwei; Hui, Ming; Kirubaharan, Christopher Joseph; Yu, Yang-Yang; Yong, Yang-Chun
Graphical abstract: Highlights: TA dopant was applied for in-situ fabrication of VA-PANI on electrode. VA-PANI electrode exhibited excellent electrochemical activity. VA-PANI electrode contributed to 5-fold improvement of power production from MFC. CV analysis unveiled EET mechanism between Shewanella and PANI electrode. Abstract: Electrode modifications with conductive and nanostructured polyaniline (PANI) were recognized as efficient approach to improve interaction between electrode surface and electrogenic bacteria for boosting the performance of microbial fuel cell (MFC). However, it still showed undesirable performance because of the challenge to control the orientation (such as vertical alignment) of PANI nanostructure for extracellular electron transfer (EET). In this work, vertically aligned polyaniline (VA-PANI) on carbon cloth electrode surface were prepared by in-situ polymerization method (simply tuning the ratio of tartaric acid (TA) dopant). Impressively, the VA-PANI greatly improved the EET due to the increased opportunity to connect with conductive proteins. Eventually, MFC equipped with the VA-PANI electrodes delivered a power output of 853 mW/m 2, which greatly outperformed those electrodes modified with un-oriented PANI. This work provided the possibility to control the orientation of PANI for EET and promise to harvest energy from wastewater with MFC.